Investigation of radiological properties and water equivalence of polymer gel dosimeters in the energy range 0.1-10 keV - Levet, Aytac; Thakur, Sonika; Kaur, Parminder; Rafiei, Mustafa Mohammad; Parsaei, Sara; Buyukyildiz, Mehmet (Korean Nuclear Soc, 2025)
The interaction parameters of radiation with matter are crucial for accurately determining radiation doses in diagnostic and treatment. This study examined the radiological features of normoxic polymer gels used to measure radiation doses. The mass attenuation coefficient (MAC), mass energy-absorption coefficient (MEAC), effective atomic number (Zeff), half value layer (HVL) and mean free path (MFP) for these samples were determined in the energy range of 0.1 keV-10 keV. Zeff was established using direct and interpolation methods. The largest discrepancy for Zeff between the methods was observed for water, with a 48 % difference in the energy range of 0.3 keV-0.5 keV. MACs of the samples were compared with Monte Carlo simulation results based on FLUKA 4-3.1 code. MAC results obtained with simulation showed good agreement with Hubbell, and the maximum and minimum differences between them were seen in the FAT sample as 8.31 % and 0.08 %, respectively. Additionally, dose rate, gamma constant, and air kerma values were calculated using mass energy absorption coefficients for all samples and their water equivalence was evaluated in the relevant energy range. It was observed that the samples with radiological water equivalence and air kerma values close to 1 were PAGAT, MAGIC, MAGAS, and MAGAT.
Keywords: Normoxic polymer gels; Radiological parameters; Monte Carlo simulation